Memorial docente - SILVA, Waldiane Pacheco (2019)
The present memorial dominates an autobiographical approach of my scholastic and professional paths, and great expressive reflections that emphasize my understanding within the educational universe, contracted of the singularized and pluralized knowledge coming from the educational context, relating the comments I mentioned with the theoretical contributions of some thinkers, enabling my reconstruction of a new vision launched on the role of teaching characterizing my perspectives and subjectivities on education based on the formation of a society devoid of social injustice.